The neurobiological substrate of intelligence: Anatomical and functional characteristics of the brain associated with cognitive abilities - Τόμπρου, Δήμητρα-Μαρία; Ντόλκα, Ελένη; Παπαδάτου-Παστού, Μαριέττα (Psychology: the Journal of the Hellenic Psychological Society, 2017)
The modern era of brain imaging has enabled the direct investigation of the neurobiological substrate of intelligence thus contributing significantly to our understanding of individual differences in cognitive functions. This is a review of recent findings on the anatomical and functional underpinnings of intelligence. Specifically, the anatomical features of the brain that are associated with intelligence are brain volume, cortical thickness, white matter microstructure, and corpus callosum thickness. The functional characteristics associated with intelligence are the degree of activation of the prefrontal cortex and other areas of the parieto-frontal network, nerve conduction velocity, rate of glucose metabolism, and direction of cerebral laterality. Two recent neurobiological theories of intelligence, namely the neural efficiency hypothesis and the parieto-frontal integration theory (P-FIT), are also presented.